Determinan Kepuasan Peserta BPJS Ketenagakerjaan pada Pelayanan Program Jaminan Kecelakaan Kerja RS Tingkat IV Lhokseumawe - Teguh Suharto; Neni Ekowati Januariana; Yuniati Yuniati; Siti Khoiriah H.D (Jurnal Kesehatan Amanah, 2024)
The establishment of the Employment Social Security Administration Agency (BPJS) on January 1, 2014 is a transformation of PT. Social Security as stipulated in Law No. 40 of 2004 concerning the National Social Security System (SJSN). This study aims to find out the factors that affect the satisfaction of BPJS Employment participants in the service of the Work Accident Insurance Program at Lhokseumawe Level IV Hospital. The method is quantitative with cross-sectional desaign. The study sample was 30 inpatients visiting Lhokseumawe Level IV Hospital taken in January-July 2024. The results of the study with Multivariate Analysis have the most dominant influence of the five variables, namely assurance with a sig value of 0.006. There is a relationship between tangibles, reliability, responsiveness, emphaty, assurance and the satisfaction of BPJS Employment Participants in the Service of the Work Accident Insurance Program, while the results of the study with Multivariate Analysis showed the most dominant influence of the five variables, namely assurance with a sig value of 0.006. Lhokseumawe Level IV Hospital to intensely conduct counseling to increase counseling so that patients can use BPJS employment health services.